2018
DOI: 10.1016/j.aju.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The age of robotic surgery – Is laparoscopy dead?

Abstract: IntroductionRobot-assisted laparoscopic surgery (RALS) has become a widely used technology in urology. Urological procedures that are now being routinely performed robotically are: radical prostatectomy (RP), radical cystectomy (RC), renal procedures – mainly partial nephrectomy (PN), and pyeloplasty, as well as ureteric re-implantation and adrenalectomy.MethodsThis non-systematic review of the literature examines the effectiveness of RALS compared with conventional laparoscopic surgery for the most relevant u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…RAUR has also been attempted for pediatric VUR; however, no consensus currently exists and RAUR has been found to have higher complication rates and lower success rates than the open approach in some reports. [ 68 ]…”
Section: Resultsmentioning
confidence: 99%
“…RAUR has also been attempted for pediatric VUR; however, no consensus currently exists and RAUR has been found to have higher complication rates and lower success rates than the open approach in some reports. [ 68 ]…”
Section: Resultsmentioning
confidence: 99%
“…According to a non‐systematic review by Schwaibold et al. , 4 there was high‐quality evidence that the robot‐assisted technique has better efficacy in terms of radical prostatectomy and partial nephrectomy, where the robot could replace conventional laparoscopy. As for reconstructive surgery, such as pyeloplasty and ureteral replantation, there appears to be an advantage in terms of surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, besides the obvious aesthetic advantages, the laparoscopic ileal ureter replacement technique also offers more recovery advantages than the traditional open repair technique 3 . It has also been reported that robot‐assisted laparoscopic surgery (RALS) is as safe as open surgery, and it is superior to open techniques with respect to intraoperative estimated blood loss (EBL) and postoperative recovery in a variety of reconstructive urological procedures 4 . However, there have only been a few reports with a limited number of ileal ureter cases 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, with more and more surgical procedures being performed with a laparoscopic technique nowadays, patients are frequently placed in a Trendelenburg position in combination with the establishment of a pneumoperitoneum (4,5). This results in an increased airway and endotracheal cuff pressure (4).…”
Section: Methodsmentioning
confidence: 99%